Upaya Meningkatkan Hasil Belajar PPKN Siswa Melalui Model Pembelajaran Discovery Learning di Kelas X IPS 1 SMAN 1 Candung - Erawati Erawati (Journal on Education, 2023)
This study aims to disclose information and discuss Efforts to Improve Students' PPKn Learning Outcomes Through the Discovery Learning Learning Model in Class X IPS/1 SMAN 1 Candung. This research is included in the type of classroom action research (CAR). This research was carried out at SMA Negeri 1 CKL, Agam Regency. The time of this research was carried out in the odd semester of the 2021/2022 school year starting in October 2021. The subjects referred to as the action in this research were class X IPS/1 students of SMA Negeri 1 Cdungung, totaling 20 people with a composition of 11 men and women as many as 9 people. The research procedure consisted of two cycles with two meetings in each cycle. Each cycle consists of four stages of research namely planning, implementation, observation and reflection. Data collection in this study was carried out using field notes, student worksheets, written tests, and documentation. The data analysis technique uses the proportion formula. The results of this study indicate that the Discovery Learning learning model has a positive impact on improving student learning outcomes. This can be seen from the understanding and mastery of student material that has been conveyed by the teacher so far (learning completeness increased from Pre-cycle, cycle I and cycle II, namely 25%, 60% and 85% respectively by giving gifts.